Over and undernutrition in the children of Australian immigrants: Assessing the influence of birthplace of primary carer and English language use at home on the nutritional status of 4–5-year-olds - Oldroyd, J; Riggs, E; Waters, E; Renzaho, C; Renzaho, A; Burns, C (My University, 2011)
Objective. To document the relationship between childhood nutrition status and ethnicity (defined as the birthplace of primary carer and English language use at home) using a nationally representative sample of 4- to 5-year-old children. Design and participants. Cross-sectional population survey of 4 983 4- to 5-year-old children (2 537 boys and 2 446 girls) as part of Wave 1 (2004) of the Longitudinal Study of Australian Children. Main outcome measures. Overweight/obesity and thinness using the newly published body mass index cut-off points of Cole (2007). Results. In total, 20.6% (95%CI 19.5, 21.7) of children aged 4 to 5 years were estimated to be overweight or obese, while 1.0% (95%CI 0.8, 1.3) was thin. Unadjusted analyses showed a significant relationship between childhood overweight/obesity and primary carer's country of birth (χ2=15.9, p<0.01), but the significance became minimal after adjusting for socio-economic and demographic factors. The adjusted model suggests that boys of primary carer's born in Europe (excluding UK and Ireland) were less likely to be overweight/obese than boys whose primary carers were born in Australia, but the overall effect size was negligible. No difference was found for girls. In addition, boys who mainly spoke English at home were less likely to be overweight/obese (OR=0.49; 95%CI 0.27, 0.88; p=0.017) and thin (OR=0.27; 95%CI 0.12, 0.62; p=0.002) than boys who spoke a language other than English at home. No difference was found for girls. Conclusions. There is a relationship between main language spoken at home and nutritional status in 4–5-year-old boys but not girls. The use of English language at home may be a protective factor for normal weight in young boys. After adjustment for socio-economic and demographics characteristics, there was a negligible relationship between overweight/obesity in children and their primary carer's country of birth.
Keywords: Child Development -- Physical; Culture; Childhood and child development; Child Development; Culture; Physical; Childhood and child development